Studies on the maturation and spawning habits of some common clupeoids of Lawson’s Bay, Waltair - Dharmamba, M (Indian Journal of Fisheries, 2016)
Clupeoid fishes, chiefly represented by the sardines (Sardinella spp.), the whitebaits (Anchoviella spp.), the anchovies (Thrissocles spp.) and the rainbow sardines (Dussumieria spp.), form an important fishery at Lawson’s Bay, Waltair and the catch statistics for a period of seven years (1950-56) show that on an average about 393 tons of these fishes are landed annually constituting about 37-5 per cent, of the total catch. The sardines rank first in importance and form on an average about 22 per cent, of the total catch.